Policy options for healthy care provisioning for unformed security force memebers. - Radebe, Mokhethi (My University, 2014)
This research report examines problems faced in health care provisioning for members of the Defence department (based on public sector lines), and Safety and Security and Correctional Services departments (based on private sector lines). This provisioning is entirely financed by Government. The aim is to determine the most viable solutions to tire specific health service delivery problems confronting these departments that will meet public health objectives. Data was collected from primary and secondary sources and interviews were conducted. Main findings indicated that increasing costs made private health care provision unsustainable. Downsizing of the defence force has resulted in under utilisation of health facilities. Recommendations are made for a public-private health care mix at the primary level and public provisioning at secondary and tertiary levels combined with members’ contributions for dependants. The active participation of providers and users as well as political will is needed for successful implementation.